Alternative disinfection methods to chlorine for use in the fresh-cut industry - Ana Meireles (2016)
The use of chlorine as a disinfectant in the fresh-cut produce industry has been identified as a concern mainly dueto public health issues. In fact, this chemical, commonly used as hypochlorous acid and hypochlorite, has alreadybeen prohibited in some European countries, due to the potential production of toxic by-products, such as chloroform and other trihalomethanes, chloramines and haloacetic acids. The search for alternative methods of disinfection is therefore a current and on-going challenge in both Academia and Industry. Some methods are welldescribed in the literature on the disinfection of food-contact surfaces and process water and also on the decontamination of the produce. These methods are commonly classified as biological (bacteriocins, bacteriophages,enzymes and phytochemicals), chemical (chlorine dioxide, electrolyzed oxidizing water, hydrogen peroxide,ozone, organic acids, etc) and physical (irradiation, filtration, ultrasounds, ultraviolet light, etc). This review provides updated information on the state of art of the available disinfection strategies alternative to chlorine thatcan be used in the fresh-cut industry. The use of combined methods to replace and/or reduce the use of chlorineis also reviewed.